Vulnerable Road User needs towards ITS - Daniel Bell; Ralf Risser (Transactions on Transport Sciences, 2017)
Due to fast development of new technologies in the field of Intelligent Transport Systems (ITS) a number of new research topics arise, especially in view of vulnerable road users (VRUs). While most advancements in the ITS sector are primarily targeting motorised transport with focus on safety and ecological aspects of transport, there is still a lack of both research and innovation considering VRUs. The vulnerable road users and ITS (VRUITS) project, co-funded by the European Commission, aims at actively integrating the "human" element into the ITS approach. The focus of this paper is on the mixed methods approach applied in the project to assess both actual user needs and expert opinions on perceived barriers and necessary adaptations on technological, societal and behavioural levels for a successful and sustainable deployment of new technologies.